Analysis of dynamic effects during high-speed forging of sintered preforms - Singh S.; Jha A.K. (My University, 2025)
This paper discusses the various technological aspects of high-speed forging of sintered preforms. The relationship between the frictional stress at the interface and other process variables is discussed and an analysis has been done for the estimation of die load by energy method taking barrelling into consideration in addition to the inertial forces for axial symmetry and plane strain sinter-forging conditions. Results are discussed critically to illustrate the interaction of various processing parameters involved during high-speed forging of sintered preforms and are presented graphically. © 2001 Published by Elsevier Science B.V.